2013
DOI: 10.1136/bcr-2013-008707
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic metastasis: a rare cause for prosthetic loosening

Abstract: SUMMARYMalignant periprosthetic metastasis is a very rare yet important cause of painful joint arthroplasty. This study presents a case in which periprosthetic osteolysis following total hip replacement (THR) occurred as a result of metastatic mesothelioma. After a THR and revision THR, histopathology confirmed the diagnosis of metastatic mesothelioma. Primary lesion was identified using CT scan of the chest. Patient is receiving palliative chemotherapy. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…These cases involved metastatic disease from the following primary malignancies: 5 cases of bronchogenic carcinoma; 3 cases of renal cell carcinoma; 2 cases of ovarian carcinoma; and 2 cases of breast cancer, gastric adenocarcinoma, malignant immunoblastic lymphoma, non-Hodgkin's lymphoma, thoracic mesothelioma, hepatocellular carcinoma, and prostate cancer (Table 1). [1,515]…”
Section: Discussionmentioning
confidence: 99%
“…These cases involved metastatic disease from the following primary malignancies: 5 cases of bronchogenic carcinoma; 3 cases of renal cell carcinoma; 2 cases of ovarian carcinoma; and 2 cases of breast cancer, gastric adenocarcinoma, malignant immunoblastic lymphoma, non-Hodgkin's lymphoma, thoracic mesothelioma, hepatocellular carcinoma, and prostate cancer (Table 1). [1,515]…”
Section: Discussionmentioning
confidence: 99%
“…It is of particular interest that this patient presented with constant pain and continuous falls because of difficulty bearing weight for 11 months before there was radiographic evidence of a permeative lytic lesion. Only a handful of cases presented at pain onset with normal radiographic findings, followed by rapid progression of osteolysis 11,13,14,[16][17][18] . Interestingly, the only other case that presented a similar period between pain onset and radiographic evidence of destruction was an SCC of the lung with metastasis about a total hip arthroplasty 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Although exceedingly rare, cases of arthroplasty failure because of metastatic spread of a distant primary malignancy exist in literature. The first report of a metastatic tumor adjacent to a total joint arthroplasty was in 1986, and several publications have since followed [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Yet, within these, only 3 reports follow a TKA 7,13,18 and involved patients with chronic pain and radiographic evidence of osteolysis at presentation.…”
mentioning
confidence: 99%
“…Only a few studies have previously reported metastasis around orthopedic implants, and most of these reports were confined to implants of total arthroplasty or plates [2,3]. The reported cases of metastasis around orthopedic implants have originated from non-Hodgkin's lymphoma, malignant fibrous histiocytoma, immunoblastic lymphoma, carcinomas of the lung, gastric carcinoma, endometrial carcinoma, ovarian carcinoma, RCC, hepatocellular carcinoma, and prostate cancer [2][3][4]. Although various cancers have been reported, no definite common denominator exists among cases of metastasis.…”
Section: Discussionmentioning
confidence: 99%